La infografía en el Diario El Río y su incidencia en el aprendizaje de los estudiantes de la carrera de comunicación social de la Universidad Técnica de Babahoyo Extensión Quevedo - Cadena Rosero, David Arturo (2019)
The present alternative proposes to the computer graphics as an educational tool so that young people who follow the career of communication can be illustrated with the example of Diario el Rio. For this, a systematic study has been proposed analyzing and evaluating the information obtained during the research project. with clear specific objectives that opened the way for the conclusions and recommendations that are made to propose a broad proposal according to the variables that are specific to you is the infographic and its influence on learning. The infographic is an ally of the information a style journalistic that every day has a greater use in the media, technology is one of its best allies in the capture of images drawings or diagrams that capture the attention of the reader. During the research process, the methodology and modality that allowed us to know more about the problem of the computer graphics used by the newspaper El Rio and how it affects the learning of communication students was applied, through bibliographic research and field it was extended and related in a direct the variables involved in this case, applying the deductive, analytical and statistical methods is selected in a concrete way the most relevant information that allows a survey and interview of what the students think about the infographic that uses this written medium of communication.